"Studio of Realism": On the Need for Art in Exhibitions on Migration History - Barbara Wolbert (Forum: Qualitative Social Research, 2010)
This essay takes "Projekt Migration" as point of departure and as a model—an exhibition on the history of labor migration to Germany and on European border politics, which contained both everyday life objects and art works. It concentrates on the materiality of the objects on display and challenges contemporary history scholars' and public historians' approaches, which rely primarily on artifacts, such as documents and objects of daily use, when they represent migration processes and immigrants' lives. The stories associated with these objects often allude to immigrants' everyday practices during their first years abroad. Transforming them into "eternal migrants," exhibits thus tend to create fictionalizations of immigrants, which are then read as realistic and neutral representations. Artists, unlike museum curators, sign their work and thus assume responsibility for the narratives and allusions, which evoke emotions in the viewers. They insert a critical distance between the viewers and the objects, and thus make the "cultural spaces" (LIPPARD, 2003) between object, author, and viewer perceptible. The generalized "othering" of the immigrants and the voyeuristic stance of the viewers towards these others' migratory fates can thus be avoided. Works of art in exhibitions on migration history enable and force the visitors, with or without migration backgrounds, to take position themselves as well. This article therefore argues for the need of artists' interventions in exhibitions on migration history. URN: urn:nbn:de:0114-fqs1002345